Effects of ipragliflozin, a selective sodium–glucose co-transporter 2 inhibitor, on blood pressure in Japanese patients with type 2 diabetes mellitus: a pooled analysis of six randomized, placebo-controlled clinical trials - Kashiwagi, Atsunori (Diabetol Int, 2016)
Our aim was to examine the effects of ipragliflozin, a selective sodium–glucose co-transporter 2 inhibitor, on blood pressure in Japanese patients with type 2 diabetes mellitus (T2DM). We conducted a pooled analysis of double-blind trials of Japanese T2DM patients, randomized to 50 mg ipragliflozin or placebo, with patient-level data for the change in systolic blood pressure (SBP) and diastolic blood pressure (DBP) from baseline to end of treatment (12–24 weeks). Data from six trials were analyzed: ipragliflozin was administered as monotherapy in two; in combination with metformin, pioglitazone, or sulfonylurea in one each; and in combination with prior therapy in patients with renal impairment in one. Overall, 628 and 368 patients were treated with ipragliflozin and placebo, respectively. The placebo-adjusted mean changes (95 % confidence interval) in SBP and DBP (mmHg) were −2.8 (−4.4, −1.3, P < 0.001) and −1.6 (−2.7, −0.6, P < 0.002), respectively, in all patients. The reductions in SBP and DBP were significantly greater in patients with baseline SBP ≥140 mmHg [−5.5 (−9.1, −1.8) and −2.9 (−5.3, −0.5), respectively] than in patients with SBP <140 mmHg [−2.1 (−3.8, −0.4) and −1.3 (−2.5, −0.1), respectively]. The reductions in SBP and DBP were also significantly greater in the ipragliflozin group than in the placebo group in patients treated with [−2.8 (−5.1, −0.4) and −2.4 (−4.0, −0.8), respectively] or without [−3.0 (−5.0, −1.0) and −1.0 (−2.4, 0.4), respectively] concomitant antihypertensive therapy. In conclusion, this pooled analysis showed that ipragliflozin was associated with significant reductions in SBP and DBP compared with placebo. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13340-016-0283-x) contains supplementary material, which is available to authorized users.